أساليب التعزيز و علاقتها بالثقة بالنفس لدى عينة من الطلبة السنة الثالثة لسانس بكلية العلوم الاجتماعية دراسة ميدانية بقسم علم النفس و علوم التربية و الأرطفونيا بجامعة عمار ثليجي الأغواط - بوداود زينب; سركو أحلام; ملياني عبد الكريم (My University, 2018)
This study aims to discovering the relationship between Reinforcement techniques &Self-confidence in student’s third year (Bachelor’s degree) at faculty social science ,university of Laghouat 2017/2018.also to figure out the differences in both scales (reinforcement techniques & selfconfidence) returns to the variable such as sex (males & females),age ,specialization. We used descriptive method with tow scales, the first one for (reinforcement techniques) which prepared by (Boudawood.Z & Sercou.A) And to confirm their psychometric properties ,than the scound one was(self-confidence /sidny shruger 1990).where it applied to random sample ,estimated about (100) students, therefor the study data was processed by statistical program (spss21). The result of this study presented that there is There is a statistically significant relationshipbetween the Reinforcement techniques &Selfconfidence. And decrease in level of self- confidence in the study sample, more of that there is not differences in Reinforcement techniques a cause to sex,age,specialization. there is not differences in of self- confidence a cause to sex ,age ,specializationMethods of reinforcement - self-confidence - university student